HUBUNGAN PEMBELAJARAN KREATIF GURU DAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN AGAMA - Juwinner Kasingku; Novensia Ronga (Nusantara Hasana Berdikari, 2022)
This quantitative research aims to examine the relationship between teacher’s creative learning and the active learning of students on religious subjects. Data were obtained through data collection from 106 respondents of Airmadidi 1 High School students. Research results show that teacher’s creative learning is at a high level. The same level is also indicated by the level of active learning of students on religious subjects. Then the relationship between teacher’s creative learning and the activeness of learning in religious subjects has no significant relationship. This explains that the students in this study did show a high level of learning activeness, but creative learning from the teacher was not a factor that caused the high activity of student learning. The recommendations in this study are for the next researchers to be able to use the same method, research design and research questionnaire, as well as different dependents, different respondents and different levels of education. Because it does not rule out the possibility of getting different results because the research was carried out at different places, respondents and times.